ANALYSIS OF OUTCOME-BASED HEALTHCARE FINANCING MODELS BASED ON INTERNATIONAL EXPERIENCE - Samandarov Dostonbek (Modern American Journals, 2025)
This article analyzes value- and outcome-based healthcare financing models using the examples of Sweden, Germany, Austria, and South Korea. It emphasizes the role of PREMs and PROMs indicators in evaluating the performance of medical institutions and staff. The paper also discusses the feasibility of implementing such models in Uzbekistan, along with the required infrastructural prerequisites.
Keywords: Outcome-based financing, PREMs, PROMs, quality of medical services, international experience.